Bayesian inference with incomplete knowledge explains perceptual confidence and its deviations from accuracy - Koosha Khalvati (Nature Portfolio, 2021)
A Bayesian framework based on partially observable Markov decision processes (POMDPs) not only predicts subjects’ confidence in a perceptual decision making task but also explains well-known discrepancies between confidence and choice accuracy as arising from incomplete knowledge of the environment.